2017
DOI: 10.1089/brain.2017.0493
|View full text |Cite
|
Sign up to set email alerts
|

Aging-Related Microstructural Alterations Along the Length of the Cingulum Bundle

Abstract: The aim of this study was to investigate the aging-related structural changes of the cingulum, one of the major components of the limbic network, which has a critical role in emotion, attention, and memory. Thirty-five healthy young adults (22.3 ± 2.7 years) and 33 healthy older adults (69.5 ± 3.5 years) were recruited. Diffusion weighted imaging data were acquired with a b-value = 2000 sec/mm and 61 diffusion directions and 4 non-weighted images. The fiber directions in each voxel were based on the constraine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 31 publications
3
16
0
Order By: Relevance
“…The small number of voxels showing associations of age with FA and RD in the hippocampal branch of the cingulum, and the lack of any association with AD or MD indicates this region of white matter is less affected than other white matter tracts. Similar to our findings, a study comparing young and older healthy adults found differences in the subgenual branch of the cingulum but no change in any diffusion measures in the parahippocampal segment of the cingulum [57].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The small number of voxels showing associations of age with FA and RD in the hippocampal branch of the cingulum, and the lack of any association with AD or MD indicates this region of white matter is less affected than other white matter tracts. Similar to our findings, a study comparing young and older healthy adults found differences in the subgenual branch of the cingulum but no change in any diffusion measures in the parahippocampal segment of the cingulum [57].…”
Section: Discussionsupporting
confidence: 91%
“…We also found a small number of voxels showing a positive linear correlation of age with AD. Both increases and decreases of AD with age have been reported [20, 23, 33, 57]. Animal studies have attributed decreases in AD to acute axonal injury [13, 58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies suggest that aging does not affect the cingulum uniformly but that region-specific effects can be observed. Some of the evidence is consistent with an age-related gradient along the long axis of the cingulum, in which frontal parts of the bundle appear most affected ( Catheline et al, 2010 ; Mårtensson et al, 2018 ; Sibilia et al, 2017 ; Yoon et al, 2008 ; see for review Chua et al, 2008 ). For example, older versus younger adults exhibited lower FA and AD as well as increased RD in the left subgenual cingulum, but not in the retrosplenial or parahippocampal cingulum ( Sibilia et al, 2017 ).…”
Section: Diffusion Mri (Dmri) Studies Of the Human Cingulum Bundlementioning
confidence: 75%
“…Some of the evidence is consistent with an age-related gradient along the long axis of the cingulum, in which frontal parts of the bundle appear most affected ( Catheline et al, 2010 ; Mårtensson et al, 2018 ; Sibilia et al, 2017 ; Yoon et al, 2008 ; see for review Chua et al, 2008 ). For example, older versus younger adults exhibited lower FA and AD as well as increased RD in the left subgenual cingulum, but not in the retrosplenial or parahippocampal cingulum ( Sibilia et al, 2017 ). Similarly, Jang et al (2016) investigated age differences across five portions of the cingulum (anterior, anterior superior, posterior superior, posterior and inferior cingulum) in 90 participants between 20 and 78 years of age.…”
Section: Diffusion Mri (Dmri) Studies Of the Human Cingulum Bundlementioning
confidence: 75%